Effect of Phosphate Fertilization and Manganese Application on Growth and Yield of Broadbean - BADAWY, FARIDA H.; EL-GAYED, O. (The Libyan Journal of Agriculture, 2023)
A field experiment was conducted in the Faculty of Agriculture Experimental Farm in Tripoli to test the effect of superphosphate fertilization, at the rates 500 and 750 kg/ha, and manganese application, as a seed soaking solution or as a foliar spray on the growth and yield of broadbean. Phosphate fertilization at the rates tested gave highly significant increases in the fresh and dry weights of the plants, seed yield and size of seeds. Nodulation of the plants was not affected by the phosphate fertilization. However, the nitrogen content of leaves was significantly increased by superphosphate fertilization at the rate of 750 kg/ha. Manganese application, either as seed soaking solution or as foliar spray had no significant effect on fresh and dry weights of plants. Manganese foliar spray significantly reduced the yield of seeds. There was no interaction between the phosphate fertilization and the manganese application.